2020
DOI: 10.1159/000506599
|View full text |Cite
|
Sign up to set email alerts
|

In Different Voices: The Views of People with Disabilities about Return of Results from Precision Medicine Research

Abstract: KeywordsDisability · Precision medicine research · Return of results · Medicalization · Marginalization Abstract Purpose: Returning genetic results to research participants is gaining momentum in the USA. It is believed to be an important step in exploring the impact of efforts to translate findings from research to bedside and public health benefits. Some also hope that this practice will incentivize research participation, especially among people from historically marginalized communities who are commonly un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Our results are consistent with those from international research which found potential or enrolled genomic research participants to have a high interest in receiving individual genetic results for medical, familial, reproductive and/or personal reasons (8,11,14,(24)(25)(26)(27). For example, in Sanderson and colleagues's study, most individuals from the general public wanted to receive individual genetic results for reasons such as, 'to motivate changes in lifestyle, to seek medical intervention, to prepare for the future, for curiosity, interest in genetics, to provide risk information to other family members, as well as for their future potential children and family planning' (11).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are consistent with those from international research which found potential or enrolled genomic research participants to have a high interest in receiving individual genetic results for medical, familial, reproductive and/or personal reasons (8,11,14,(24)(25)(26)(27). For example, in Sanderson and colleagues's study, most individuals from the general public wanted to receive individual genetic results for reasons such as, 'to motivate changes in lifestyle, to seek medical intervention, to prepare for the future, for curiosity, interest in genetics, to provide risk information to other family members, as well as for their future potential children and family planning' (11).…”
Section: Discussionsupporting
confidence: 90%
“…Limited literature documents the views of marginalised groups in research, however there is some evidence suggesting that marginalised groups from the global north have differing views. Most recently, in the US, Sabatello, Zhang, Chen and Appelbaum (2020) found that interest in receiving biological and health-related individual genetic results from precision medicine research varied signi cantly across gender, race/ethnicity and disability groups (14). In their study, most participants reported an interest in receiving genetic risk results about 'a treatable disease', like asthma (68%) and 'an untreatable disease' like Alzheimer's (61%) (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies we include also focused on patients with other diseases or disabilities. These were patients with chronic inflammatory diseases [ 71 ], chronic kidney disease [ 72 ], patients without a diagnosis, but with conditions presumed to be genetic (“diagnostic odyssey”) [ 64 ], patients with a chronic condition such as diabetes mellitus, hypercholesterolemia or hypertension [ 73 ], drug users (heroin, crack, cannabis) [ 74 ], patients with rare diseases [ 75 ] and people with disabilities [ 76 78 ]. Some studies did not provide any information about the condition of the patients included in the study.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, studies show that teachers can play as important roles as parents in empowering teenagers to make healthy choices, including in the context of mental health [37,52], but also that existing curricula in schools are not up-to-date with existing knowledge of genomics [53]. As empowerment is a relational process [54], teens' and their families' and communities' experiences of social marginalization (e.g., poverty, which is disproportionally high among underserved racial/ethnic minorities [55]), and bias in health care may affect their engagement in genomic discussions, as found in studies of African American and Latino adults [56][57][58][59][60]. Stigma surrounding psychiatric genetics and teenagers' experiences with psychiatric conditions (personally or through family history) may further affect the degree of empowerment and extent of supports they need.…”
Section: Discussionmentioning
confidence: 99%